2018
DOI: 10.1002/cncr.31706
|View full text |Cite
|
Sign up to set email alerts
|

Results of an early access treatment protocol of daratumumab in United States patients with relapsed or refractory multiple myeloma

Abstract: Background Daratumumab is a human CD38‐directed monoclonal antibody indicated for the treatment of relapsed and refractory multiple myeloma (MM). Methods A multicenter, open‐label treatment protocol provided early access to daratumumab for patients who had progressive MM after they received ≥3 prior lines of therapy that included a proteasome inhibitor and an immunomodulatory agent or if they were refractory to both a proteasome inhibitor and an immunomodulatory agent. Patients received daratumumab 16 mg/kg we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 19 publications
12
25
2
Order By: Relevance
“…To decrease the IRR rate, one trial tested the addition of 10 mg of montelukast as a premedication prior to the first daratumumab infusion and found the IRR rate was one-third lower in patients who received this leukotriene inhibitor[8]. Beyond slowing the infusion rate, no other clinical trial has successfully reported any intervention to decrease the IRR rate[9].…”
mentioning
confidence: 99%
“…To decrease the IRR rate, one trial tested the addition of 10 mg of montelukast as a premedication prior to the first daratumumab infusion and found the IRR rate was one-third lower in patients who received this leukotriene inhibitor[8]. Beyond slowing the infusion rate, no other clinical trial has successfully reported any intervention to decrease the IRR rate[9].…”
mentioning
confidence: 99%
“…For patients experiencing IRs, the infusion should be held and can be restarted at the starting infusion rate after the IR has subsided and the patients’ symptoms have resolved or returned to the baseline . Our institutional experience led to the inclusion of 10 mg of oral montelukast in our protocol as a pre‐infusion medication for the first dose of daratumumab administration . No dose reductions are needed for daratumumab during rechallenging for the next cycle.…”
Section: Managing Daratumumab‐related Toxicities and Practical Aspectsmentioning
confidence: 99%
“…Finally, Chari et al reported safety results from a multicenter, open-label treatment protocol providing early access to daratumumab for US patients who had RRMM after ≥3 prior lines of therapy that included a PI and an IMID or who were double refractory [21]. Three hundred forty-eight patients were enrolled and received daratumumab for a median of 1.9 months (range, 0.03-6 months).…”
Section: Article Highlightsmentioning
confidence: 99%